Uso de indicadores hidrológicos para classificação de trechos de estradas florestais quanto ao escoamento superficial - De Barros Ferraz, Silvio Frosini [UNESP]; Marson, Júlio César; Fontana, Carolina Rodrigues; De Paula Lima, Walter (My University, 2007)
Forest roads are frequently pointed as source of environmental problems related to erosion and they also influence harvest cost due to maintenance operations. Roads not well designed are sources of hydrological problems on catchments and the current attention to sustainability of forest exploration projects point out to the need of diagnostics tools for guiding the redesign of the road system. At this study, runoff hydrological indicators for forest road segments were assessed in order to identify critical points of erosion and water concentration on soils. A road network of a forest production area was divided into 252 road segments that were used as observations of four variables: mean terrain slope, main segment slope, LS factor and topographic index. The data analysis was based on descriptive statistics for outliers' identification, principal component analysis and for variability study between variables and between observations, and cluster analysis for similar segments groups' identification. The results allowed classifying roads segments into five mains road types: road on the ridge, on the valley, on the slopes, on the slopes but in a contour line and on the steepest slope. The indicators were able to highlight the most critical segments that differ of others and are potential sources of erosion and water accumulation problems on forest roads. The principal component analysis showed two main variability sources related to terrain topographic characteristics and also road design, showing that indicators represent well those elements. The methodology seems to be appropriated for identification of critical road segments that need to be redesigned and also for road network planning at new forest exploration projects.
Using hydrological indicators for runoff assessment on forest road segments
Keywords: Erosion; Geographic information system; Hydrological modeling; Forest road; Hydrological indicators; Road network; Runoff assessment; Geographic information systems; Hydrology; Principal component analysis; Roads and streets; Forestry; Forests; GIS; Roads